Case Study of Job Insecurity Among Malaysian Employees with Technology Involvement in Shared Services Center (SSC) Industry - Yeoh Wee Win Yeoh (MultiTech Publisher, 2023)
The study had been intended to explore the case study of the job insecurity arises among the Malaysian employees in aligned with the advancement in the technology development in the shared services center (SSC) industry in Malaysia. It is known that the trend of SSC had been creating the wave in Malaysia due to the ideal location with rich in professional talents and resources leveraging the higher quality of SSC bult up in Malaysia. However, the involvement of the technology advancement had created not only the increase in the deliveries of SSC but also rising the concerns among the employees. The automation and artificial intelligence (AI) had been the major threats towards the job insecurity among the employees as the concerns arises for the employees in losing the significant role in the organization. Therefore, the current study had explored the relationship between the technology involvement against the job insecurity among the employees in the SSC industry with Malaysian market. The quantitative study had been assisted with the distribution of 150 questionnaires to the target study of the employees of SSC in Malaysia. The outcome of the study had shown the result where the impact of the technology involvement in SSC industry had proven the positive relationship presence against the job insecurity. In other words, the employees are highly concerns with the increasing application of technology in the workplace and business process. This had certainly draw out the concerns to be highlighted into the SSC industry to develop the strategic planning to assist the adoption process of the technology in SSC industry in Malaysia